PENERAPAN MODEL PEMBELAJARAN TREFFINGER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SEMESTER II SDN 2 DEMUNG-BESUKI KECAMATAN BESUKI KABUPATEN SITUBONDO TAHUN PELAJARAN 2017/2018 - Franita Luki Hardiyati; Indah Lestari Setiorini (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2018)
Low learning activities have an impact on the low learning outcomes of students, especially in Mathematics lessons. One of the factors is the use of model / learning method that is not in accordance with the characteristics of students in the class so as to make students feel bored, bored and not enthusiastic in following the learning activities. The purpose of this research is to improve the learning outcomes of Mathematics through the application of the Treffinger learning model in the third grade students of SDN 2 Demung-Besuki Semester II Lesson Year 2017/2018. The type of research used is Classroom Action Research (PTK), using a research model design developed by Kemmis and Mc. Taggart consisting of 4 stages, including: planning (plan), action (acting), observation (observing) and relection / analysis (reflection). The research instrument used in this research are interview method, observation, test and documentation. From the results of observation before the action obtained mastery learning students reached 57.14%, while in the first cycle increased by 76.19%. This shows that the application of the Treffinger learning model in cycle I has not been successful so that it is continued in cycle II. The result of learning mastery analysis in cycle II was obtained equal to 85,71%. It shows that the application of learning model Treffinger can improve student learning outcomes Mathematics students both individually with a score of ≥ 70% and classically with a score of 80%. Based on the results of research and analysis of the discussion that has been implemented, it can be taken a conclusion that the application of learning model Treffinger can improve learning outcomes Mathematics in third grade students SDN 2 Demung-Besuki Semester II Lesson 2017/2018